Anterior Pelvic Exenteration for Chemo-irradiated Non-diethylstilbestrol Exposed Clear Cell Vaginal Cancer - BACALBASA, NICOLAE (In Vivo, 2019)
Background/Aim: Clear cell vaginal adenocarcinomas are rare tumors occurring in women which are usually treated by chemo radiotherapy with good outcomes. However, in certain cases, this treatment is not associated with complete response and a further surgery is needed. Case Report: We present the case of a 38-year-old patient diagnosed with stage IVA clear cell vaginal cancer who had been previously submitted to radio chemotherapy and in whom the lesion persisted after the oncological treatment; therefore, the patient was proposed for surgery with curative intent. The tumor was resected by performing an anterior pelvic exenteration with good outcomes, the patient being discharged in the seventh postoperative day. At one-year follow-up the patient remains free of recurrent disease. Conclusion: Pelvic exenteration with curative intent might be the option of choice for persistent locally advanced clear cell vaginal cancer.